2002
DOI: 10.1021/jo0163041
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties and Absolute Rate Constants for β-Scission of Ring-Substituted Cumyloxyl Radicals. A Laser Flash Photolysis Study

Abstract: A laser flash photolysis study of the spectral properties and beta-scission reactions of a series of ring-substituted cumyloxyl radicals has been carried out. All cumyloxyl radicals display a broad absorption band in the visible region of the spectrum, which decays on the microsecond time scale, leading to a strong increase in absorption in the UV region of the spectrum, which is attributed to the corresponding acetophenone formed after beta-scission of the cumyloxyl radicals. The position of the visible absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
125
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(146 citation statements)
references
References 14 publications
19
125
2
Order By: Relevance
“…In this context, it is, however, important to point out that a recent product and time-resolved kinetic study carried out by some of us has clearly shown that the para-(2,2-diphenylcyclopropyl)cumyloxyl radical (1 Å ) exists in equilibrium with a 2,2-dimethyl-1-oxaspiro [2,5]octadienyl radical (2 Å ). 19 Cumyloxyl radicals are known to undergo C-CH 3 b-scission as the exclusive unimolecular reaction (Scheme 2, path a), 6f,6g, 20,21 and the failure to observe the O-neophyl rearrangement (Scheme 2, path b) reasonably reflects the lower stability of the 2-phenoxy-2-propyl radical as compared to the 1-phenoxy-1-phenylalkyl one displayed in Scheme 1.…”
mentioning
confidence: 99%
“…In this context, it is, however, important to point out that a recent product and time-resolved kinetic study carried out by some of us has clearly shown that the para-(2,2-diphenylcyclopropyl)cumyloxyl radical (1 Å ) exists in equilibrium with a 2,2-dimethyl-1-oxaspiro [2,5]octadienyl radical (2 Å ). 19 Cumyloxyl radicals are known to undergo C-CH 3 b-scission as the exclusive unimolecular reaction (Scheme 2, path a), 6f,6g, 20,21 and the failure to observe the O-neophyl rearrangement (Scheme 2, path b) reasonably reflects the lower stability of the 2-phenoxy-2-propyl radical as compared to the 1-phenoxy-1-phenylalkyl one displayed in Scheme 1.…”
mentioning
confidence: 99%
“…This result was explained by a transition state effect, where the transition state is more polar than the radical and is thus more stabilized by interactions with polar and polarizable solvents. Furthermore, the β-scission of cumyloxyl radicals measured using laser flash photolysis also showed a rate increase with increasing solvent polarity 63 Figure 7. The E T parameter represents the charge-transfer absorption of the solvent in pyridinium N -phenolbetaine and serves as a different measure of solvent polarity than the dielectric constant 66 .…”
Section: β-Scissionmentioning
confidence: 93%
“…16 In acetonitrile solution, small differences in the rate constant were measured after ring substitution, with the k β values for the different radicals ranging between 7.1 × 10 5 and 1.1 × 10 6 s -1 (Table 1). This behavior suggests that substituent effects operate in the same direction on both the cumyloxyl radical and the transition state for β-scission that is characterized by an incipient acetophenone-like character.…”
Section: Methodsmentioning
confidence: 99%
“…12, 16 Very interestingly, a red-shift in λ max (vis) was also observed for cumyloxyl and ring-substituted cumyloxyl radicals on going from acetonitrile to protic solvents such as methanol, 5e 2,2,2-trifluoroethanol (TFE) 15 and water, 16,18 with the shift increasing in the order: MeOH < TFE < H 2 O. Compared to acetonitrile, no variation in the position of λ max (vis) was observed in other protic solvents such as acetic acid and tertiary alkanols, and in a variety of aprotic solvents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation